Insect-specific viruses: transmission dynamics and biological control strategies against arboviruses - Wilkman, Lukas; Kaarle, Elin; Luande, Verah Nafula; Lantto, Rebecca; Evander, Magnus; Lwande, Olivia Wesula (Frontiers in Microbiology, 2025)
Mosquitoes are known to vector arthropod-borne viruses (arboviruses) that pose a global public health issue in the form of mosquito-borne viral diseases such as chikungunya fever, dengue fever, Japanese encephalitis, yellow fever, and Zika. Besides, mosquitoes may also carry insect-specific viruses (ISVs), which are evolutionarily alike arboviruses yet do not infect vertebrates. These ISVs have been shown to affect the ability of mosquitoes to transmit arboviruses, as well as potentially inhibit arbovirus infections in vertebrate hosts. Yet, ISVs still constitute a relatively new and little-researched area where further studies may yield new knowledge regarding their distribution, their future importance in the control of mosquito-borne viral disease and potential role in biological control of mosquitoes. This review provides insights into ISV classification, transmission, and biology, as well as historical and future aspects. It mainly focuses on the characterization of the transmission dynamics of ISVs to highlight the various potential arboviral pathogen transmission blocking mechanisms along with evolution and host tropism. The review also provides additional information on the potential use of ISVs as a method of biological control in comparison to other proposed methods as well as delving into current research into arbovirus-based vaccines and antiviral drug development.